The Evolving Landscape of PD-1/PD-L1 Pathway in Head and Neck Cancer - Qiao, Xin-wei; Jiang, Jian; Pang, Xin; Huang, Mei-chang; Tang, Ya-jie; Liang, Xin-hua; Tang, Ya-ling (Frontiers in Immunology, 2020)
Over the past ten years, cancer immunotherapy has made significant progress in multiple cancer types and gradually been applied to clinical cancer care, in which the programmed cell death protein-1 (PD-1)/programmed cell death ligand 1 (PD-L1) pathway is one of the most attractive targets. Compared with traditional therapies, the emerging PD-1/PD-L1 blockade immunotherapy exhibited more satisfactory curative effects and lower toxicity for patients with advanced head and neck squamous cell carcinoma (HNSCC). This review analyzes the expression characteristics and clinical significance of PD-1/PD-L1 in HNSCC, the immunosuppressive roles of tumor cell and stromal cell expressing PD-1/PD-L1 in this disease, and present development landscape of PD-1/PD-L1 inhibitors, which may provide new curative alternatives for recurrent or metastatic HNSCC.